1987
DOI: 10.2135/cropsci1987.0011183x002700060016x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Different Amylose Levels in Rice1

Abstract: Amylose content has a pronounced effect on the cooking and eating quality of rice (Oryza sativa L.). Inheritance of amylose content in five crosses of rice and their reciprocals involving low, intermediate, and high amylose parents was studied. The analysis was based on single grains in the parent, F1, F2, B1F1 and B2F1 generations. The genes for high amylose content were found to be completely dominant over those for low or intermediate amylose content. Low or intermediate amylose content in the crosses teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…It is directly associated with volume expansion and water absorption during cooking and with hardness, whiteness and dullness of cooked rice. Genetic studies have indicated that the nonwaxy trait dominates over the waxy trait (Kumar and Khush, 1987). Among nonwaxy parents, high amylose is completely dominant over low or intermediate amylose, and intermediate is dominant over low (Kumar and Khush, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is directly associated with volume expansion and water absorption during cooking and with hardness, whiteness and dullness of cooked rice. Genetic studies have indicated that the nonwaxy trait dominates over the waxy trait (Kumar and Khush, 1987). Among nonwaxy parents, high amylose is completely dominant over low or intermediate amylose, and intermediate is dominant over low (Kumar and Khush, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have indicated that the nonwaxy trait dominates over the waxy trait (Kumar and Khush, 1987). Among nonwaxy parents, high amylose is completely dominant over low or intermediate amylose, and intermediate is dominant over low (Kumar and Khush, 1987). The statistical results pertaining to amylose content of different rice variants are presented in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to vary from virtually 0 to about 30 per cent in the cultivars around the world. Unlike other cereals, people of various regions prefer to eat certain types of rice (Kumar & Khush, 1987). This obviously means that precise levels of amylose have to be bred into new varieties to satisfy local preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The range of amylose contents for the waxy varieties measured in Table 2 fell within the very low amylose class (Kumar & Khush, 1987). Based on these results, it is easy to conclude that waxy rice grains do have some amount of amylose molecules despite the absence of GBSSI expression within the grains of these varieties.…”
Section: The Molecules Of Amylosementioning
confidence: 68%
“…It is measured in breeding programs as soon as heterozygosity is minimised and is the first tool used in the selection process for eating quality. Rice varieties are classified into high (>25%), intermediate (20 -25%), low (10 -19%), very low (3 -9%), or waxy (0 -2%) amylose classes (Kumar & Khush, 1987).…”
Section: Amylose Contentmentioning
confidence: 99%